Cyber Security Audit in Information Technology Governance: A Literature Review and Future Research Agenda - Saifudin, Saifudin; Fachriaz, Nazri Sidqi (Jurnal Transformatika, 2026)
This study aims to examine cyber security audits in information technology governance (ITG) more deeply using a literature review approach. The method used in this research is a systematic literature review by applying PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analysis) method approach with 25 years of observation from 1999 to 2024. 980 articles were obtained, nevertheless, only 36 articles were eligible. The research results show that cyber security audit is compatible and closely related to information technology governance (ITG), mainly the domain regarding the need for the board of directors to understand and to master cyber security audit skills to overcome violations and data leaks in IT governance. Cyber security audit and information technology governance (ITG) are two key components to maintain information security as well as to manage information technology effectively. Integration between the two in a conceptual framework helps organizations identify, manage and mitigate cyber risks and maintain alignment with business objectives.